Production Stock Monitoring System at PT Yamaha Indonesia Using the Scrum Method - Rizkina Maulida Safira; Chanifah Indah Ratnasari (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
Digital transformation brings changes to the industrial sector to become Industry 4.0. PT Yamaha Indonesia is a piano-manufacturing company that also uses technology to help monitor the production of piano parts. Production stock monitoring is carried out in order to meet the company's production targets. As a result, the company's stock can meet customer demand, keeping inventory costs to a minimum. Furthermore, it has the potential to optimize operational production time. Previously, the production monitoring procedure was done manually. Recordings are made every few hours or so to keep track of the data. Due to the manual recording of each step of the piano's part-making process, productivity and the ability to perform other tasks are slowed down. To address these issues, PT Yamaha Indonesia, through this research, developed a production stock monitoring system. This system was built using the Scrum method and implements data visualization using chart.js to facilitate monitoring. The research contribution is analyzing user needs until the production stock monitoring system is built so that monitoring the manufacturing process can be simplified and more efficient, and it can be done in real-time.